Kardiochirurgia Dorosłych Temporary subclavio-femoral bypass used for surgical treatment of thoraco-abdominal aneurysms - Siondalski, Piotr; Jaworski, Łukasz; Jarmoszewicz, Krzysztof; Pawlaczyk, Rafał; Brzeziński, Maciej; Jagielek, Dariusz; Rogowski, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Introduction: Surgical treatment of descending aorta aneurysms including the thoraco-abdominal part of the aorta is one of the most extensive surgical procedures and is associated with many complications and high mortality. The most common complications are: multiorgan failure and spinal cord ischaemia. Aim: The aim of this study was to present theoretical bases and results of surgical treatment of thoraco-abdominal aneurysms using subclavio-femoral temporary bypass. Material and method: 3 patients were operated on in our department due to thoraco-abdominal aneurysm (Crawford type I and II). In all cases subclavio-femoral temporary bypass was used. Results: Obtained results were satisfying. Conclusions: The presented method improves the operation’s safety and result of surgical treatment of thoraco-abdominal aneurysms. This can be ascertained based on our preliminary experience and analysis.